Left myocardial performance index in monochorionic diamniotic twin pairs complicated by selective fetal growth restriction with abnormal umbilical artery Doppler. (2nd September 2021) - Ortiz, Javier U.; Torres, Ximena; Bennasar, Mar; Eixarch, Elisenda; Gómez, Olga; Crovetto, Francesca; Lobmaier, Silvia M.; Martinez, Josep M.; Gratacós, Eduard; Crispi, Fatima
Abstract: Objective: To evaluate left myocardial performance index (MPI) and its time intervals in monochorionic diamniotic (MCDA) twin pairs complicated by selective fetal growth restriction (sFGR) with abnormal (persistent ‐type II‐ or intermittent ‐type III‐ absent or reversed end‐diastolic flow) umbilical artery Doppler. Methods: Retrospective study including 16 MCDA twin pairs with sFGR type II, 26 MCDA twin pairs with sFGR type III and 42 gestational age‐matched uncomplicated MCDA twin pairs in a single tertiary center. Left isovolumetric contraction time (ICT), ejection time (ET), and isovolumetric relaxation time (IRT) were measured and MPI calculated by conventional Doppler at diagnosis of sFGR. Results: In sFGR type II, the smaller twin had shorter ET and prolonged IRT and MPI, while the larger twin showed prolonged ICT and MPI as compared to uncomplicated MCDA twins. In sFGR type III, the smaller twin had shorter ICT and ET, while the larger twin showed prolonged ICT, IRT, and MPI in comparison to controls. Conclusion: A differential pattern of MPI time intervals could be observed in MCDA twins with sFGR type II and III. All twins had echocardiographic signs of pressure/volume overload, except the smaller twin type III with shorter systolic times probably reflecting reduced volume load.